The Effect of Unconventional Fiscal Policy on Consumption – New Evidence Based on Transactional Data - Winfried Koeniger; Peter Kress (Institute of Labor Economics (IZA), 2024)
We use novel transaction-level card expenditure data to estimate the effect of the temporary value-added tax (VAT) cut in Germany 2020. We find that the annualized growth rate of expenditures for durables increased by 6 percentage points (pp) during the tax cut, with a particularly strong increase of up to 11 pp for consumer electronics. The expenditure growth rate for semi-durables and non-durables did not change by and large. The estimates imply a consumption multiplier of 0.2 and an elasticity of fiscal revenues to a VAT rate reduction of two thirds.
Keywords: D12; E21; E62; E65; H31; 330; consumption expenditure; transactional data; temporary VAT cut; unconventional fiscal policy